Stout camphor tree genome fills gaps in understanding of flowering plant genome evolution - Chaw, Shu-Miaw; Liu, Yu-Ching; Wu, Yu-Wei; Wang, Han-Yu; Lin, Chan-Yi Ivy; Wu, Chung-Shien; Ke, Huei-Mien; Chang, Lo-Yu; Hsu, Chih-Yao; Yang, Hui-Ting; Sudianto, Edi; Hsu, Min-Hung; et al. (Nature plants, 2019)
We present reference-quality genome assembly and annotation for the stout camphor tree ( Cinnamomum kanehirae (Laurales, Lauraceae)), the first sequenced member of the Magnoliidae comprising four orders (Laurales, Magnoliales, Canellales and Piperales) and over 9,000 species. Phylogenomic analysis of 13 representative seed plant genomes indicates that magnoliid and eudicot lineages share more recent common ancestry than monocots. Two whole-genome duplication events were inferred within the magnoliid lineage: one before divergence of Laurales and Magnoliales and the other within the Lauraceae. Small-scale segmental duplications and tandem duplications also contributed to innovation in the evolutionary history of Cinnamomum . For example, expansion of the terpenoid synthase gene subfamilies within the Laurales spawned the diversity of Cinnamomum monoterpenes and sesquiterpenes. A high-quality reference genome of the stout camphor tree reveals its genome evolution and supports that magnoliid and eudicot lineages share more common ancestry relative to monocots.